Validity and Practicality of Integrated Student Worksheets (LKPD) Using the Project-Based Learning Model on the Mangrove Ecosystem to Improve Students' Science Process Skills - Marjanah; Elfrida; Nuraini; Nurhasnah Manurung (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to produce Student Worksheets (LKPD) integrated with the Project Based Learning model on the mangrove ecosystem material to improve valid and practical science process skills. This study uses the ADDIE development model (analysis, design, development, implementation, and evaluation). The research parameters measured are the validity and practicality of the LKPD. Validity is reviewed from the presentation, content, and language. Practicality is reviewed from the implementation of student activities during the learning process using the LKPD. Data analysis of this study was carried out descriptively quantitatively. Based on the results of the study, the validity of the LKPD was 94% with very valid criteria. The practicality of the LKPD based on the implementation of the LKPD was 90.01% with very good criteria and the student response aspect obtained an average of 92.36% with very good criteria. Thus, the Student Worksheet (LKPD) integrated with the Project Based Learning model is considered valid and practical so it is suitable for use in the learning process.